The Routledge handbook of tourism and sustainability - Gossling, Stefan; Hall, Colin Michael, 1961-; Scott, Daniel, 1969- (Abingdon, Oxon ; New York, N.Y. : Routledge, 2015)
"Sustainability remains one of the major issues in tourism today. Concerns over climate and environmental change, the fallout from the global economic and financial crisis, and the seeming failure to meeting UN Millennium development goals have only reinforced the need for more sustainable approaches to tourism, however they be defined. Given the centrality of sustainability in tourism curricula, policies, research and practice it is therefore appropriate to prepare a state of the art handbook on the relationship between tourism and sustainability. This timely Handbook of Tourism and Sustainability is developed from specifically commissioned original contributions from recognised authors in the field, providing a systematic guide to the current state of knowledge on this area. It is interdisciplinary in coverage and international in scope through its authorship and content. The volume commences with an assessment of tourism's global environmental, e.g. climate, emissions, energy use, biodiversity, water use, land use, and socio-economic effects, e.g. economic impacts, employment and livelihoods, culture. This then provides the context for the following sections that describe the main theoretical frameworks and constructs that inform tourism and sustainability, management tools and approaches, and the approaches used in different tourism and travel industry sectors. The book concludes by examining emerging and future concerns in tourism and sustainability such as peak-oil, post-carbon tourism, green economy and transition tourism"--
1. Tourism and sustainability : an introduction / C. Michael Hall, Stefan Gossling and Daniel Scott -- 2. The evolution of sustainable development and sustainable tourism / C. Michael Hall, Stefan Gossling and Daniel Scott -- 3. The global effects and impacts of tourism : an overview / Michelle Rutty. [et al.] -- 4. Tourism and the precautionary principle in theory and practice / David A. Fennell -- 5. Sustainable yield : an integrated approach to tourism management / Jeremy Northcote -- 6. Tourism and common pool resources / Helen Briassoulis -- 7. Tourism and human rights / Freya Higgins-Desbiolles and Kyle Powys Whyte -- 8. Ethics in tourism / Georgette Leah Burns -- 9. Pro-poor tourism : reflections on past research and directions for the future / Dao Truong -- 10. Environmentally sustainable tourists? / Sara Dolnicar -- 11. Environmental justice and tourism / Rob Hales and Tazim Jamal -- 12. Consumptive and non-consumptive tourism practices : the case of wildlife tourism / Brent Lovelock -- 13. Tourism and cultural change / Melanie Kay Smith -- 14. Environmental indicators and benchmarking for sustainable tourism development / Heather Zeppel -- 15. Certification and labeling / Sonya Graci and Rachel Dodds -- 16. Life cycle assessment / Viachaslau Filimonau -- 17. Carbon management / Stefan Gossling -- 18. Sustainable tourism legislation and regulation / John M. Jenkins and Mucha Mkono -- 19. Promoting voluntary behaviour change for sustainable tourism : the potential role of social marketing / Dao Truong and C. Michael Hall -- 20. Managing visitors to the natural environment / David Newsome and Susan Moore -- 21. Tourism and corporate social responsibility / Tim Coles, Emily Fenclova and Claire Dinan -- 22. Wildlife tourism : "Call it consumption!" / James Higham and Debbie Hopkins -- 23. Stories of people and places : interpretation, tourism and sustainability / Gianna Moscardo -- 24. Tourism in the future(s) : forecasting and scenarios / Daniel Scott and S
Keywords: Sustainable tourism -- Handbooks, manuals, etc